Penggunaan Media Pembelajaran “Puppet” untuk Meningkatkan Kemampuan Bercerita Peserta Didik Sekolah Dasar - Ermawaty, Susy; Pratiwi, Veronika Unun (Jurnal Didaktika Pendidikan Dasar, 2025)
The use of media in storytelling learning activities that have not been adjusted to the characteristics of students can cause students' storytelling skills to be low. The purpose of the research is to improve students' storytelling skills in Indonesian subjects by using "Puppet" learning media. The research method used is Classroom Action Research. The subject of the study was 10 students of Class III of SD Negeri Gemantar 3 Mondokan Sragen. The research data was collected by observation technique using observation sheet instruments. The research data was analyzed in a quantitative descriptive manner. Based on the data from the research results, it can be seen that students' storytelling skills have improved. Students who are able to tell stories during Pre-Cycle (20%), Cycle I (40%), and Cycle II (90%), so that the increase in students' storytelling ability from Pre-Cycle to Cycle I is 20% and Cycle I to Cycle II is 50%. Thus, it can be concluded that the use of "Puppet" learning media can improve students' storytelling skills in Indonesian Language Learning.